VviRafS5 Is a Raffinose Synthase Involved in Cold Acclimation in Grapevine Woody Tissues - Noronha, Henrique; Silva, Angélica; Silva, Tiago; Frusciante, Sarah; Diretto, Gianfranco; Gerós, Hernâni (Frontiers in Plant Science, 2022)
The accumulation of raffinose family oligosaccharides (RFOs) in response to cold stress is mediated by galactinol (GolS) and raffinose synthases (RafS), but the role of these enzymes in the cold acclimation of grapevine (Vitis vinifera L.) woody tissues is still unclear. To address this gap in the literature, one-year lignified grapevine canes were incubated at 4 ºC for 7 and 14 days and tissues were analyzed for sugar content and gene expression. Results showed that starch breakdown correlated with soluble sugars accumulation, including sucrose, glucose, fructose, raffinose and stachyose. Remarkably, ABA levels increased during cold acclimation, which correlated with the increased expression of the key ABA-synthesis genes VviNCED2 and VviNCED3. Expression analysis of the VviGolS and VviRafS family allowed the identification of VviRafS5 as a key player in grapevine cold response. The overexpression of VviRafS5 in Saccharomyces cerevisiae allowed the biochemical characterization of the encoded protein as a raffinose synthase with 87 kDa. In grapevine cultured cells, VviRafS5 was up-regulated by cold and ABA but not by heat and salt stresses.